Does health insurance contribute to improving responsiveness of the health system?: The case of elderly in rural Tanzania - Amani, Paul Joseph (Umeå University, 2026)
Background: Financing healthcare in Tanzania has for years depended on out-of-pocket payments. This mechanism has been criticized as being inefficient, contributing to inequity and high cost as well as denying access to healthcare to those most in need, including the elderly in rural areas. Health insurance (HI) was recently introduced as an instrument to enable equitable access to healthcare and thus to improve the responsiveness of the health system. Even though health insurance is expected to bring benefits to those who are insured, there is a lack of specific studies in the country looking at the role of HI in facilitating the health system responsiveness among vulnerable populations of remote areas. Aim: The aim of this thesis is to understand if and how health insurance contributes to improving the responsiveness of the healthcare system among the elderly in rural Tanzania. Methods: Four interrelated sub-studies (2 quantitative and 2 qualitative) were conducted in Igunga and Nzega districts of Tabora region between July 2017 and December 2018. The first two sub-studies are based on a household survey using an adapted version of the World Health Organization’s Study on Global Ageing and Adult Health questionnaire. Elderly people aged 60 years and above who had used both outpatient and inpatient healthcare three and twelve months prior to the study, respectively, were interviewed. Whereas in sub-study 1 the focus was to investigate the role of health insurance status on facilitating access to healthcare, sub-study 2 assessed the relationship between health insurance and the health system responsiveness domains. In sub-study 3, interviews with healthcare providers were carried out to capture their perspective regarding the functioning of the health insurance. In the final sub-study 4, focus group discussions with elderly were conducted in order to explore their experience of healthcare, depending on their health insurance status. Crude and adjusted logistic and quantile regression models were applied to analyse the association between health insurance and access to healthcare (sub-study 1) and responsiveness (sub-study 2), respectively. For both sub-studies 3 and 4, qualitative content analysis was used to analyse the data. Results: Sub-studies 1 and 2 involved a total of 1899 insured and uninsured elderly, while sub-studies 3 and 4 included 8 health providers and 78 elderlies respectively. Sub-study 1 showed that about 45% of the elderly were insured and HI ownership improved access and utilization of healthcare, both outpatient and inpatient services. In sub-study two, however, health insurance was associated with a lower responsiveness of the healthcare system. In general, all six domains: cleanliness, access, confidentiality, autonomy, communication, and prompt attention were rated high, but three were of concern: waiting time; cleanliness; and communication. Sub-study 3 uncovered several challenges coexisting alongside the provision of insurance benefits and thus contributing to a lower responsiveness. These included shortage of human resources and medical supplies, as well as operational issues related to delays in funding reimbursement. In sub-study 4, the elderly revealed that HI did not meet their expectations, it failed to promote equitable access, provided limited-service benefits and restricted use of services within residential areas. Conclusion: While HI seems to increase the access to and use of healthcare services by the elderly in rural Tanzania, a lower responsiveness by the healthcare system among the insured elderly was reported. Long waiting times, limited-service benefits, restricted use of services within schemes, lack of health workforce in both numbers and skills as well as shortage of medical supplies were important explanations for the lower responsiveness. The results of this thesis, while supporting the national aim of expanding HI in rural areas, also exposed several weaknesses that require immediate attention. There is a need to, first, review the insurance policy to improve its implementation, expand the scope of services coverage, and where possible, to introduce cross-subsidization between the publicly owned schemes; additionally, improvements in the healthcare infrastructure, increasing the number of qualified health workforce and the availability of essential medicines and laboratory services, especially at the primary healthcare facilities, should be prioritized and further investments allocated.